The bone code [compact disc, unabridged] - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series., 2021)
A storm has hit South Carolina, dredging up crimes of the past. On the way to Isle of Palms, a barrier island off the South Carolina coast, forensic anthropologist Temperance Brennan receives a call from the Charleston coroner. During the storm, a medical waste container has washed up on the beach. Inside are two decomposed bodies wrapped in plastic sheeting and bound with electrical wire. Chillingly, Tempe recognizes many details as identical to those of an unsolved case she handled in Quebec fifteen years earlier. With a growing sense of foreboding, she flies to Montreal to gather evidence and convince her boss Pierre LaManch to reopen the cold case. She also seeks the advice, and comfort, of her longtime beau Andrew Ryan. Meanwhile, a storm of a different type gathers force in South Carolina. The citizens of Charleston are struck by a bacterium that, at its worst, can eat human flesh.